2022
DOI: 10.1038/s41467-022-33203-1
|View full text |Cite
|
Sign up to set email alerts
|

E-cigarettes and their lone constituents induce cardiac arrhythmia and conduction defects in mice

Abstract: E-cigarette use has surged, but the long-term health effects remain unknown. E-cigarette aerosols containing nicotine and acrolein, a combustion and e-cigarette byproduct, may impair cardiac electrophysiology through autonomic imbalance. Here we show in mouse electrocardiograms that acute inhalation of e-cigarette aerosols disturbs cardiac conduction, in part through parasympathetic modulation. We demonstrate that, similar to acrolein or combustible cigarette smoke, aerosols from e-cigarette solvents (vegetabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 82 publications
1
14
0
2
Order By: Relevance
“…Acrolein, as an unsaturated aldehyde, is the most reactive of the common aldehydes present in industrial manufacturing, fuel combustion and tobacco burning (Carll et al., 2022; Destaillats et al., 2002; Sithu et al., 2010). It poses a strong negative inhalation health effect due to its chronic RfC of 0.02 μg/m 3 (the lowest among VOC species), compared to 1,3‐butadiene (2 μg/m 3 ) and chloroethane (10,000 μg/m 3 ) (Faroon et al., 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Acrolein, as an unsaturated aldehyde, is the most reactive of the common aldehydes present in industrial manufacturing, fuel combustion and tobacco burning (Carll et al., 2022; Destaillats et al., 2002; Sithu et al., 2010). It poses a strong negative inhalation health effect due to its chronic RfC of 0.02 μg/m 3 (the lowest among VOC species), compared to 1,3‐butadiene (2 μg/m 3 ) and chloroethane (10,000 μg/m 3 ) (Faroon et al., 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Mice exposed to various e-liquid constituents and aerosols (PG, VG, PG/VG, and tobacco- and menthol-flavored commercial e-liquids) showed significantly decreased HR during flavored e-cig exposures. 83 PG/VG-derived e-liquids caused the greatest changes in HR in male mice and showed no changes in female mice. Male mice also showed significantly increased HRV during flavored e-cig exposures, again with no changes observed in female mice.…”
Section: Effects On Neurological Activation Of the Cardiovascular Systemmentioning
confidence: 87%
“…These changes were then followed by increased HR and decreased HRV between exposures and postexposure in males with no observable changes in females. 83 A recent study from Nabavizadeh et al 84 suggested that no individual constituent of e-cigs or traditional cigarettes was responsible for endothelial dysfunction but that inhaled particles induce vagal nerve signaling initiated by airway irritation. These studies indicate that different components of e-cigs, including but not limited to e-liquid and nicotine, as well as biological characteristics, such as sex and metabolic comorbidities, all interact to predispose e-cig users to adverse cardiovascular outcomes.…”
Section: Effects On Neurological Activation Of the Cardiovascular Systemmentioning
confidence: 99%
“…42 JUUL Labs, Inc.© was dominating the e-cigarette market at the time of this study and remains nowadays among the five top-selling brands. 43 Similar to cigarette smoke 31, 44 and prior generation (tank-style) e-cigarette aerosol, 24, 25, 28, 45 particulates and gases produced by pod-mod devices access the body primarily through the respiratory system yet retain the ability to modulate biological processes in other organs. 46, 47 Related to the cardiovascular system, acute inhalation of pod-mod e-cigarette aerosol increases the augmentation index (arterial stiffness), reduces the reactive hyperemia index (endothelial vasodilator function), and raises peripheral blood pressure in occasional users.…”
Section: Discussionmentioning
confidence: 99%